Asceticism - Wimbush, Vincent L.; Valantasis, Richard, 1946- (Oxford University Press, 2002)
From meditation and fasting to celibacy and anchoritism, the ascetic impulse has been an enduring and complex phenomenon throughout history. Offering a sweeping view of this elusive and controversial aspect of religious life and culture, Asceticism looks at the ascetic impulse from a unique vantage point. Cross-cultural, cross-religious, and multidisciplinary in nature, these essays provide a broad historical and comparative perspective on asceticism - a subject rarely studied outside the context of individual religious traditions. The work represents the input of more than forty preeminent scholars in a wide range of fields and disciplines, and analyzes asceticism from antiquity to the present in European, Near Eastern, African, Asian, and North American settings.; Asceticism is organized around four major themes that cut across religious traditions: origins and meanings of asceticism, which explores the motivations and impulses behind ascetic behaviors; hermeneutics of asceticism, which looks at texts and rhetorics and their presuppositions; aesthetics of asceticism, which documents responses evoked by ascetic impulses and practices, as well as the arts of ascetic practices themselves; and politics of asceticism, which analyzes the power dynamics of asceticism, especially as regards gender, cultural, and ethnic differences. Critical responses to the major papers ensure the focus upon the themes and unify the discussion. Two general addresses on broad philosophical and historical-interpretive issues suggest the importance of the subject of asceticism for wide-ranging but serious cultural-critical discussions. An Appendix, Ascetica Miscellanea, includes six short papers on provocative topics not related to the four major themes, and a panel discussion on the practices and meanings of asceticism in contemporary religious life and culture. A selected bibliography and an index are also included.; The only comprehensive reference work on asceticism with a multicultural, multireligious, and multidisciplinary perspective, Asceticism offers a model not only for an understanding of a most important dimension of religious life, but also for future interdisciplinary study in general.